Complementary interventions for cognitive rehabilitation in patients with cerebral palsy: a single-center study - Ammara Rafique (Bulletin of Faculty of Physical Therapy)
Abstract Background Cerebral palsy (CP) is a neuromotor disorder that impairs a person’s ability to balance, stand, maintain posture, and walk. Research has indicated that Al Fatiha and negative air ion (NAI) are beneficial for ameliorating several behavioral, spiritual, physical, and societal issues. The objective of the present study was to assess the effect of Al Fatiha and NAI interventions on cognitive skills using Lumosity software. Methods This randomized control trial was conducted et al.-Umeed Rehabilitation Association, Karachi, Pakistan, between February and April 2021, following ethical approval (Ref: IBC-2017) from the University of Karachi. CP patients who volunteered for the study were randomly assigned to either the control group or to groups receiving interventions involving Al Fatiha and NAI exposure. Due to the limited number of consents obtained, participants were selected without consideration of age, cognition level, gender, mobility, motor type, and additional impairments. While all groups continued their regular therapies, the intervention groups underwent 31 structured sessions over a period of 6 weeks. Five Lumosity games were selected to assess the cognitive performance of all inducted participants in the three groups. Statistical analysis including paired t-tests, one-way analysis of variance (ANOVA), and post hoc tests was conducted using SPSS version 28 to compare outcomes among the three groups. Results Paired t-tests showed that the Al Fatiha intervention significantly enhanced selective attention (1133.3 ± 584.8, p < .05) and working memory (31,036.2 ± 4013.9, p < .001), while the NAI intervention resulted in improvements in information processing (31,036.2 ± 4013.9, p < .01), selective attention (1150.0 ± 705.3, p < .01), spatial fluency (6830.7 ± 4720.0, p < .01), and spatial reasoning (8719.3 ± 3499.5, p < .01). Apart from intervention groups, only spatial reasoning was improved in the control group (9068.3 ± 3450.1, p < 0.05). One-way ANOVA and Tukey’s post hoc analysis showed significant differences among the control and intervention groups at baseline in information processing, selective attention, and spatial fluency. These cognitive functions are likely attributable to increased neuronal activity in the prefrontal cortex and elevated serotonin levels. Conclusion Based on the findings, both interventions are proposed as advanced, complementary, non-pharmacological, and cost-effective cognitive rehabilitation therapies for patients with CP. We recommend further research to validate these findings through second and third-phase clinical trials.